Peningkatan Pengetahuan Tanda Obat Tidak Layak Konsumsi Untuk Mewujudkan Penguatan Sistem Hukum Aspek Budaya - Ambar Dwi Erawati; Mona Tiorina Manurung; Chusnul Zulaika (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2023)
Advances in technology are influencing people in purchasing drugs online. Purchasing medicines online helps people in their healing efforts because it is easier to get medicines. However, purchasing drugs online is not yet legally certain to get consumer protection. So it is necessary to conduct counseling for a culture of legal awareness in purchasing drugs over the counter.  The counseling activity aims to increase cadres' knowledge about the signs that drugs are not suitable for consumption, and Cadre transmits to the community so that a culture of legal awareness is realized in purchasing drugs in free. Methods used in this activity by providing counseling (knowledge transfer). The result of this activity is that cadres' knowledge about the signs of unfit for consumption and damaged drugs has increased by 20%, Resistance about the dangers of consuming damaged drugs has increased by 45%.  Respondents' knowledge on how to choose the right drug seller increased by 25%, how to check the expiration date increased by 30%, how to check for drugs that are still good increased by 25% and how to choose drugs that can be given freely increased by 35%.  At the time of counseling, cadres have not fully implemented a spec budaya hukum, it is hoped that cadres can provide information obtained at PKK meetings within their respective RTs so as to build a legal system of cultural aspects.